Two new species of Glandularia (Verbenaceae) from Rio Grande do Sul and an updated key to the species occurring in Brazil - Thode, Verônica A.; Bordignon, Sérgio Augusto De Loreto (Phytotaxa, 2019)
Two species of Glandularia from Rio Grande do Sul Brazilian state are described, G. rupestris V. Thode & Bordignon and G. sessilifolia V. Thode & Bordignon. Detailed morphological descriptions, geographical distribution, evaluation of their IUCN conservation status and photographs are presented. Comparison tables with morphologically similar species occurring in Rio Grande do Sul and an identification key to the species occurring in Brazil are also provided.